KOMPETENSI, IKLIM ORGANISASI DAN KINERJA PEGAWAI - Dien Angraeni Sagita (JIANA ( Jurnal Ilmu Administrasi Negara ), 2016)
Competence, Organizational Climate and Employee Performance. This study aimed to determine the effect of competence and organizational climate on employee performance at the University of Riau. The study population overall employee Faculty and Rector of University of Riau as much as 104 people, samples were taken 50% of the population (for 52 people). The data collection technique using three approaches namely interviews, questionnaires and documentation study. Analysis of data using multiple linear regression analysis. The results showed that the condition of employee competence Faculty and Rector of University of Riau is a good majority (73.1%). The climatic conditions of the University of Riau is a good majority (63.5%). Competence and organizational climate partially and simultaneously influence to employee perfomance. Contribution competence and organizational climate on employee performance is 79.5% and the remaining 20.5% is determined by other factors.